Effects of robot-assisted percutaneous kyphoplasty on osteoporotic vertebral compression fractures: a systematic review and meta-analysis - Chen, Haoqian; Li, Jia; Wang, Xin; Fu, Yanming (Journal of robotic surgery, 2024)
This study systemically reviewed the effects of robot-assisted percutaneous kyphoplasty (R-PKP) on the clinical outcomes and complications of patients with osteoporotic vertebral compression fracture (OVCF). The articles published from the establishment of the database to 19 April 2024 were searched in PubMed, The Cochrane Library, Web of Science, Embase, Scopus, China National Knowledge Infrastructure (CNKI), and Chinese biomedical literature service system (SinoMed). Meta-analysis was employed to evaluate the status of pain relief and complications between the control and R-PKP groups. Standardized mean difference (SMD) or mean difference (MD), risk ratios (RR), and 95% confidence interval (CI) were selected for analysis, and a common or random effect model was adopted to merge the data. Eight studies involving 773 patients with OCVFs were included. R-PKP could effectively Cobb’s angles (MD = −1.00, 95% CI −1.68 to −0.33, P = 0.0034), and decrease the occurrence of cement leakage (RR = 0.36, 95% CI 0.21 to 0.60, P < 0.0001). However, there was no significant effect on the results of visual analog scale (MD = −0.09, 95% CI −0.20 to 0.02, P = 0.1145), fluoroscopic frequency (SMD = 5.31, 95% CI −7.24 to 17.86, P = 0.4072), and operation time (MD = −0.72, 95% CI −7.47 to 6.03, P = 0.8342). R-PKP could significantly correct vertebral angle and reduce cement leakage. Thus, R-PKP maybe an effective choice for correction vertebral Angle and reducing postoperative complications, while its impact on relieving pain, decreasing fluoroscopic frequency, and shortening operation time need further exploration.